MECHANISMS OF INDIVIDUALIZATION AND MANAGEMENT OF TRAINING LOADS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This scientific article analyzes the theoretical and practical aspects of the mechanisms for individualizing training loads and their management. The study studies effective methods for planning loads, taking into account the age, gender, level of physical fitness and functional state of athletes. It also covers the issues of optimal coordination of the volume, intensity and recovery processes during training.The article substantiates the effectiveness of load management using modern monitoring tools, testing systems and control methods. The results of the study show that individualized training is important in improving the physical and functional performance of athletes, preventing excessive fatigue and increasing sports results.
Keywords: Training load, individualization, load management, physical fitness, functional state, load volume, intensity, recovery process, monitoring, sports results, individual approach, sports training, control methods.